Seismic Behavior of Fatigue-Retrofitted Steel Frame Piers - Kinoshita, K. (Institute of Research and Community Outreach - Petra Christian University, 2013)
Fatigue retrofit works have been conducted on severely fatigue damaged beam-to-column connections of existing steel frame bridge piers in Japan. It is clear that retrofit works provides additional stiffness but the significance on the seismic behavior of steel frame piers is not clear. Since fatigue retrofit works have become prevalent, the effect of fatigue retrofit works on the seismic behavior of steel frame piers need to be understood. The objective of this study is therefore to investigate these effects of the retrofit work, especially installation of bolted splices, which is the most common technique. Elasto-plastic finite element earthquake response analyses were carried out. It is shown that the existence of bolted splices may increase seismic demand on the piers when plastic hinge zone is located on the beam. In addition, longer bolted splices using low yield strength steel are proposed to overcome this problem and are shown to give beneficial effects.